1992
DOI: 10.1007/bf00162968
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nearest neighbors on the rate and pattern of spontaneous point mutations

Abstract: The numbers and local sequence environments of the two types of substitution mutation plus additions and deletions have been obtained directly in this study from differences between a large number of extant primate gene and pseudogene sequences. A total of 3786 mutations were scored in regions where similarities between pseudogene and corresponding gene sequences is greater than or equal to 85%, comprising approximately 30% of the pseudogene database of 80,584 bp. The pattern of mutations obtained in this fash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
96
1
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 46 publications
10
96
1
3
Order By: Relevance
“…This order is different from that calculated from 3243 substitutions in gene and pseudogene sequences published by Blake et al (1992), which had C ≈ A ӷ t > g at the ‫1מ‬ site and G ӷ A > t ӷ c at the +1 site after being normalized by the average nucleotide proportion in the gene sequences. The GC content of their gene and pseudogene sequences was 57%, compared with 41% for the genome average.…”
Section: Genome Research 1683contrasting
confidence: 87%
“…This order is different from that calculated from 3243 substitutions in gene and pseudogene sequences published by Blake et al (1992), which had C ≈ A ӷ t > g at the ‫1מ‬ site and G ӷ A > t ӷ c at the +1 site after being normalized by the average nucleotide proportion in the gene sequences. The GC content of their gene and pseudogene sequences was 57%, compared with 41% for the genome average.…”
Section: Genome Research 1683contrasting
confidence: 87%
“…It has previously been shown that the mutation rate varies as a function of local context effects, particularly depending upon the adjacent nucleotides (Blake et al 1992;Zhao et al 2003;Hwang and Green 2004). Such variation in the mutation rate could lead to an increased number of triallelic SNPs if some sites have an elevated mutation in two or more pathways, e.g., if both C / T and C / A occur at higher rates.…”
Section: Excess Of Triallelic Sitesmentioning
confidence: 99%
“…The mutation rate of a site is known to depend upon the adjacent nucleotides, the best known example being the CpG dinucleotide (Coulondre et al 1978;Bird 1980) at which the frequency of both transition and transversion mutations is elevated. However, other adjacent nucleotides also influence the mutation rate (Blake et al 1992;Zhao et al 2003;Hwang and Green 2004). Furthermore, we have recently shown that there is variation in the mutation rate that does not depend upon the identity of the adjacent nucleotides or any specific context (Hodgkinson et al 2009).…”
mentioning
confidence: 98%
“…Transition mutations occur at a significantly higher rate than transversion mutations (6)(7)(8). Substitution rates depend on flanking nucleotides, a notable example being cytosine in CpG dinucleotides which, in mammals, is usually methylated at the 5-carbon and undergoes hydrolytic deamination to thymine at a relatively high rate (8)(9)(10).…”
mentioning
confidence: 99%
“…Transition mutations occur at a significantly higher rate than transversion mutations (6)(7)(8). Substitution rates depend on flanking nucleotides, a notable example being cytosine in CpG dinucleotides which, in mammals, is usually methylated at the 5-carbon and undergoes hydrolytic deamination to thymine at a relatively high rate (8)(9)(10). The germline mutation rate at CpGs is much lower within CpG islands (regions enriched in CpGs surrounding or near the transcription start sites of many genes) reflecting, at least in part, the fact that most islands are likely unmethylated in the germline (10).…”
mentioning
confidence: 99%